Optical Modules for Optical Burst Switching - Huang Shuiqing (Guangtongxin yanjiu)
【Objective】To meet the requirements of Artificial Intelligence(AI)cluster networks for flexibility in resource allocation and resource utilization, Optical Burst Switching (OBS) has returned to people’s view. More items may be required to the optical module: firstly, a nanosecond optical path switching speed is required, and the receiver of the high-speed optical module is required to adapt to burst mode. Secondly, currently high-speed optical switches that reach the nanosecond level usually have the problem of high optical path insertion loss. Therefore, the link loss of high-speed optical modules is required to meet the Extended-Reach(ER) distance standard.【Methods】To meet this requirement, the article presents the assembly of an ER optical module using a fully commercial chip with a Thin Film Lithium Niobate (TFLN) and PhotoDetector (PD) solution. A testing system has been designed for this module, and the subsequent steps of the work are still in progress.【Results】The experimental results show that an optical link budget of 20 dB is obtained, basically meeting the requirements of high-speed optical switching for optical module link budget. The OBS system is acceptable for optical modules with various particle size. We have preliminarily explored the design of three types of 100 Gbit/s lane optical modules: due to limitations in overall power consumption and volume, four wave mixing, and difficulties in coupling with multiple Avalanche PhotoDetectors(APD), the implementation of 4-way ER4 optical modules is much easier than 8-way ER8 modules. The ER2 module with two optical channels can adopt the coaxial process Electro-absorption Modulation Laser(TO-EML)+ small aperture APD scheme, which has the advantages of easy implementation, high cost-effectiveness, and mature supporting chips.【Conclusion】Therefore, 200 Gbit/s ER2 is the optimized choice for OBS systems